The effects of the type of cereal on the chemical and textural properties and on the consumer acceptance of pre-cooked, legume-based burgers. (January 2016) - Summo, Carmine; Centomani, Isabella; Paradiso, Vito M.; Caponio, Francesco; Pasqualone, Antonella
Abstract: In a future scenario where the world population will have doubled by 2050, legumes will be playing an important role in human nutrition since they are an inexpensive, protein-rich food source. In order to increase legume consumption, innovative solutions are needed to meet the needs of modern consumers. In this context, the aim of this study has been to set up pre-cooked legume-based burgers that couple high nutritional value and good sensory features and to evaluate their chemical, nutritional and textural profile, as well as the consumers acceptance based on the type of cereal used. The proposed legume-based burgers were characterized by fatty-acid and amino–acid profile fulfilling the dietary guidelines. Mono-unsaturated fatty acids accounted for about 61% of the total fatty acids, so that more than 20% of the total energy values of the burgers were provided by MUFA. Moreover, fiber content was comprised between 5.58% and 7.88% of fresh matter, so as to meet the requirements for 'high fiber' and/or for 'source of fiber' nutritional claims. Through a careful choice of the ingredient ratios we achieved a good level of consumer's appreciation, with scores higher than 6.5 for all the parameters considered, indicating good possibilities for industrial upscaling. Highlights: Innovative formulations of legume-based burgers (LB) were produced. LB were characterized by good level of appreciation by consumers. The nutrition value of LB accomplished the recent dietary guidelines. 'High/source of fiber' and 'source of protein' nutritional claims could apply to LB.